Penguatan resiliensi diri bagi korban pelecehan seksual di sekolah - Mulyanto Mulyanto; Mohammad Jamin; Hari Purwadi; Anti Mayastuti; Gayatri Dyah Suprobowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The purpose of this study is to find out that strengthening resilience can be useful to help psychologically recover for students who are victims of criminal acts of sexual harassment. Of course, it is supported by good relations from family, school and social environment as well as a strong will on the victim to try to rise from adversity due to the occurrence of the crime of sexual harassment that happened to her. The type of research used by the author is normative or doctrinal legal research that is prescriptive and applied. This research approach is carried out with a statute approach . The results of this study indicate that efforts to strengthen resilience in the context of psychologically rehabilitating victims of sexual harassment crimes are useful for helping to forget the sadness and fear and despair due to the suffering received by the victims due to the criminal acts of sexual violence committed by the perpetrators. As well as support from families, schools and the environment will greatly help victims to be enthusiastic about returning to school to achieve the goals that victims hope for in the future